Big data based architecture to bringing together graduates and recruiters: case of Moroccan University - Abdemounaime Hamdane; Nadir Belhaj; Halima El Hamdaoui; Karima Aissaoui; Moulhime El Bekkali; Nour El Houda Chaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Due to the current health crisis caused by covid 19, a negative impact has occurred on the global economy and more specifically on employability. Many people have lost their jobs or have seen their incomes drop. Nowadays, the search for job offers or potential candidates is done mainly online, where several platforms already exist (LinkedIn, Viadeo or others online recruitment systems). These solutions are particularly difficult to use due to the volume of data to be found and the manual compatibility check. In addition, the surplus of unqualified candidates and unverified resumes is a major concern of online recruiting systems. What we propose in this article is a framework that helps bridge the gap between graduates and recruiters through a big data architecture for university based on a real and certified database of graduates and companies.